Sosialisasi Financial Technology (Fintech): Cerdas Dalam Memilih Dan Memutuskan Penggunaan Aplikasi Pinjaman Dana Online - Islamiah Kamil; Dewi Anggraini; Hendi Prihanto (Universitas Prof. Dr. Moestopo (Beragama), 2022)
Online loans (pinjol) are increasingly widespread, especially during the Covid-19 pandemic. People who are experiencing economic difficulties are also trying to find alternative loans to meet urgent needs. The attitude of vigilance must also be increased in applying for this loan because many illegal loans are not registered with the Financial Services Authority (OJK). All communities, including students, need to be careful not to get caught up in the detrimental effects of illegal loans. This community service activity is expected to increase the knowledge of the participants about online loans so that they can help overcome public ignorance, especially for housewives about using online loan applications, so they can be smart in choosing and deciding to borrow funds online. This activity was carried out for 1 (one) day, namely on November 4, 2021 in the multipurpose room of residents around Duri Kosambi Cengkareng Village. The implementation method is done by giving lectures and interactive discussions. All participants gave a positive response about the socialization activities provided.